Risk assessment of dengue in Betong Sarawak using simple mathematical model - Gunap, Timothy (2020)
The dengue fever has become a major health public concern especially in tropical countries worldwide. Despite an intensive control and prevention program over the past few years by the health authorities, the dengue case is still going for an uprising trend. In Betong, the incidence cases of dengue in Betong, Sarawak has shown an upward trend from the year 2014 until 2018. Even with massive efforts in the control and prevention of Aedes mosquitos, the alarming rise of cases with large epidemics involving all the four dengue serotypes still a major concern. This paper discusses the risk assessment of dengue in Betong, Sarawak by using simple tools to predict and evaluate the dengue incidence through a risk map based on entomological data and human case parameters. We apply a mathematical model for dengue infection that takes into account vector indicators and historical incidence, in the years 2014 to 2018 of Betong, Sarawak. Moreover, this model will help us to understand how the disease is spread through individuals in the areas. The mathematical model that we use is the SEIR Model (Susceptible, Exposed, Infective and Recovered). This model is then generated into mathematical equations by calculating the risk factor in each sector of Betong from the year 2014 until 2018. After the risk-factor has been analyzed by using the model equation, we created a risk map of the five sectors in Betong District using Geographical Information System (GIS) and it is then compared between Aedes aegypti and Aedes albopictus. The risk map using GIS will help us to visualize the risk in that areas with a low or high risk of disease outbreaks and provides a systematic control measure. The study found that the Betong sector (Mean: 4.35) had the highest risk score to be exposed to Aedes aegypti followed by the Pusa sector (Mean: 2.70). The lowest risk score was detected in Spaoh (Mean: 0.45), Maludam (Mean: 0.14) and Debak (Mean: 0.06). Similar trends were also observed for Aedes albopictus where the highest risk score was also observed in Betong (Mean: 1.33) and the lowest was in Debak (Mean 0.02). In summary, the risk score was higher for Aedes aegypti as compared to Aedes albopictus. The capability to create an early warning system through risk assessment using the SEIR model and GIS provides a piece of useful information for the health authorities in the Betong district in formulating systematic strategies of dengue prevention and control programmed in the future.